Improving Loan Distribution to Farmers: Informational Needs of Mexican Banks - Robert Strong (Journal of International Agricultural and Extension Education, 2012)
The Mexican Ministry of Agriculture provides lending institutions outlooks for respective crops grown in the country. This study sought to assist in determining Mexican banks’ perceptions of the relative advantage, compatibility, complexity, trialability,and observability of agricultural information from the Ministry to aid in distributing loans to farmers. Fourteen (N = 14) agricultural loan officers from Mexican banks were interviewed to meet the study’s objectives. The majority of participants believed the Ministry’s information had a relative advantage over other sources. Complexity was the primary barrier for lending institutions not adopting the Ministry’s information. Providing the information more quickly, improved communication between both entities, and using social media were recommendations lending institutions provided the Ministry for increasing the rate of adoption of their information. Expanding the timeframe under which lending institutions receive commodity analyses from the Ministry may increase the amount of accessible finance to Mexican farmers
Keywords: Diffusion of Innovations; Mexican Banks; Ministries of Agriculture; Loan Distribution to Farmers